NOBEL PRIZES AND COMPOUNDS ORGANOMETALLIC - Santiago C., J. (2011)
The development of organometallic compounds has played an important role in the development of organic synthesis. In this article work involving organometallic compounds received the Nobel Prize in chemistry, compared with other similar works that were not awarded are discussed.